A Review of Operational Issues in Managing Physical Currency Supply Chains. Issue 6 (29th July 2016) - Geismar, H. Neil; Sriskandarajah, Chelliah; Zhu, Yunxia
Abstract : Even though more and more transactions and payments are conducted electronically, physical currency (banknotes and coins) still plays an essential role in commerce and trade, and it is expected to maintain its dominance in the near future. Over the past decade, several studies have analyzed various currency supply chains across the world. This study provides an overview of this research. The structure of a general banknote supply chain is given before the discussion of the problems from three different perspectives: (i) the supply side, that is, the parties who are in charge of supplying currency in the supply chain; (ii) the demand side, that is, the parties who request the currency; and (iii) the secure third‐party logistics providers. We also provide a framework for analyzing the US coin supply chain and descriptions of the coin supply chains in other countries. Future research directions are proposed based on the research work carried out so far and for the field in general.